PROMOTION OF AGRICULTURAL PRODUCTS AND ALCOHOLIC BEVERAGES THROUGH EUROPEAN QUALITY SCHEMES IN EU COUNTRIES FOR THE YEAR 2022 - Ţimiraş, Laura Cătălina (Studies and Scientific Researches. Economics Edition, 2022)
European quality schemes used at Community level have the role of ensuring the legal protection of agri-food products and alcoholic beverages, thus having an important promotional role. Thus, consumers perceive the products whose names are protected by means of quality schemes as having a higher value, which results in increased sales, but also in other benefits of a quantitative and qualitative nature for the producers and the area of origin. This article presents, in the first part, some aspects with regard to the impact, from a marketing perspective, of the use of quality schemes, using in particular information from literature, and subsequently renders the situation in the EU countries, at the level of 2022, regarding the number of products protected under the various quality schemes, by country and by category of protected product, using official information. Several quality schemes are used in the European Union: Geographical indications (Protected designation of origin, Protected geographical indication, Geographical indication), Traditional speciality guaranteed, Mountain product, Product of EU's outermost regions, but this paper refers only to products whose name was protected via Geographical indications and Traditionals speciality guaranteed.